Non-reflective inlet conditions for the calculation of unsteady turbulent compressible flows at low Mach number. (6th June 2014) - Moguen, Yann; Bruel, Pascal; Perrier, Vincent; Dick, Erik
<x content-type="archive" xml:space="preserve">Abstract</x> For the unsteady simulation of compressible subsonic flows (Large Eddy Simulation or Direct Numerical Simulation), the proper handling of the inlet boundary is a challenging task. Indeed, inflow generation through imposition of the velocity may lead to a non-physical reflection of the upstream acoustic waves. In the present contribution, a method that allows both filtering of these waves and proper imposition of the required variables is proposed. This method is based on identification of the roles of the temporal rate of change of wave amplitudes at the inlet in the low Mach number regime. The formulation obtained is tested numerically on unsteady one-dimensional flows at low Mach number for which the unsteady inlet velocity signal is purely harmonic or harmonic with the superimposition of synthetic turbulence.